Analisis Perencanaan Laba Di PT. Kimia Farma Trading Dan Distribution Cabang Serang - Eka Sundari Romadhona; Gerry Ganika; Fiesty Utami; Firli Agusetiawan Shavab; Titis Nistia Sari (FEB Universitas Sultan Ageng Tirtayasa, 2022)
Break even point analysis is a tool or method used by management to recognize a certain level of sales so that there is no natural profit or loss. Break even point analysis is also used to recognize the level of sales volume before the company faces a loss so that it can be used by managers to determine sales planning and profit planning. The purpose of this study is to describe the application of profit planning analysis, explain the picture of sales planning, describe the minimum sales that must be maintained and the profit planning that will be targeted in the future. Based on the results of research by PT. Kimia Farma Trading and Distribution Serang Branch in 2021 the break even point level obtained was IDR 286,264,096. The planned sales plan in 2021 is IDR 1,413,309,728, in 2022 it is IDR 657,359,478 with a profit planning of IDR 447,154,873.